2017
DOI: 10.1186/s13000-016-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Double-hit lymphomas: clinical, morphological, immunohistochemical and cytogenetic study in a series of Brazilian patients with high-grade non-Hodgkin lymphoma

Abstract: BackgroundDouble-hit lymphomas (DHL) are rare high-grade neoplasms characterized by two translocations: one involving the gene MYC and another involving genes BCL2 or BCL6, whose diagnosis depends on cytogenetic examination. This research studied DHL and morphological and/or immunophenotypic factors associated with the detection of these translocations in a group of high-grade non-Hodgkin lymphoma cases.MethodClinical and morphological reviews of 120 cases diagnosed with diffuse large B-cell lymphoma and Burki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Most of our patients with DEL or DHL had a high stage (III, IV), intermediate to high IPI, and higher extra-node involvement (P <0.001). These results matched with many previous studies (Oliveira et al, 2017;Snuderl et al, 2010;Riedell et al, 2018;Friedberg, 2017, Reagan et al, 2017.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of our patients with DEL or DHL had a high stage (III, IV), intermediate to high IPI, and higher extra-node involvement (P <0.001). These results matched with many previous studies (Oliveira et al, 2017;Snuderl et al, 2010;Riedell et al, 2018;Friedberg, 2017, Reagan et al, 2017.…”
Section: Discussionsupporting
confidence: 93%
“…In our study and among DEL patients, the morphological pattern of diffuse growth was the commonest (99%) with a "starry sky" pattern of 20% of the cases, which represented the main features of BL. In the DHL group, the typical morphology was a diffuse monomorphic pattern of numerous apoptotic bodies (Oliveira et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Most of the reported cases appear to exhibit a DLBCL morphology with a diffuse growth pattern, variable nuclear size, prominence of nucleoli, variable mitotic figures and variable proliferation rate. 1,3,8 Our case also reports similar high-grade, diffuse large B-cell lymphomalike morphologic features with that of previously reported cases.…”
Section: Discussionsupporting
confidence: 87%
“…In our work, to counterbalance the potential interpretation bias in evaluating the presence of SSP, we took four DLBCL samples per case to maximise tumour representativeness on the TMAs. In the literature, a correlation of c‐MYC /SSP was once described but this was only between SSP and c‐MYC gene rearrangement [ 47 ]. Moreover, a statistical analysis confirmed that these two factors could stratify DLBCL patients into prognostically relevant subgroups.…”
Section: Discussionmentioning
confidence: 99%